Gongola Basin Geoid Determination using Isostatic Models and Seismic Reflection Data and Geophysical Interpretation - Epuh, E.E.; Olaleye, J.B.; Omogunloye, O.G. (Геофизический журнал, 2016)
The application of Stokes’ formula to create geoid undulation requires no masses outside the geoid. Usually, a constant density of 2.67 g/cm3 is used in the determination of the geoid which introduces error in the reduced gravity anomalies (Helmert’s condensation) and consequently the geoid. In this paper, isostatic models of Airy—Heiskanen and Pratt—Hayford were utilized in the determination of the geoid by considering the planar and spherical approximation models the indirect effect of the topographic lateral density variation on the geoid was computed as additive correction for the improvement of the accuracy of the computed geoid. Additional density information deduced from seismic and well log information were considered for the variable density computation. The geopotential geoid undulations were computed from the EGM 2008 model. The residual geoid was obtained by subtracting the local isostatic geoid from the geopential geoid. Geoid and gravity admittance studies were also carried out to complement the results from the residual geoid. Применение формулы Стокса для вычисления ундуляций геоида требует отсутствия масс вне его. Как правило, постоянная плотность 2,67 г/см3 используется при определении геоида, что обусловливает ошибку в редуцированных гравитационных аномалиях (конденсация Гельмерта) и, следовательно, геоида. В работе использованы изостатические модели Эри—Хейсканена и Пратта—Хейфорда при определении геоида, рассматривая приближенные плоские и сферические модели. Рассчитан непрямой эффект изменения топографической латеральной плотности на геоиде в качестве аддитивной поправки для улучшения точности вычисленного геоида. Для расчета переменной плотности рассмотрена дополнительная информация о плотности, полученная по сейсмическим и каротажным данным. По модели EGM 2008 рассчитаны геопотенциальные ундуляции геоида. Остаточный геоид получен путем вычитания локального изостатического геоида из геопотенциального геоида. Также проведены исследования проводимости геоида и гравитационного поля в дополнение к изучению остаточного геоида.